Sistem Informasi Penjualan Daging Menerapkan Model User Centered Design Berbasis Web - Ardiyansyah, Riyan; Wahyuddin, Mohammad Iwan (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
PT. Safana Food Makmur is a business that is engaged in selling meat, whose shop is located in the city of Depok, in sales it still uses a manual transaction system so that consumers who want to buy or view available product information must come directly to the store. And for the location of the store, only a few buyers know about it because information about the store is very limited only by word of mouth. So from the existing problems, a website-based sales information system was created, this information system in its design uses MySQL for database management, PHP programming language and with the help of the Code Igniter framework. From the research resulted in a sales information system that will be used by PT. Safana Food Makmur, this system is able to assist in product sales and promotion so as to increase sales.